If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying G = 2g + -7 Reorder the terms: G = -7 + 2g Solving G = -7 + 2g Solving for variable 'G'. Move all terms containing G to the left, all other terms to the right. Simplifying G = -7 + 2g
| 3(-6-7v)= | | 12(b+3)=4(3b+3)+3b | | -2n=-3+10 | | 5-3x+4x=-5 | | (-9x^6y^4z)(y^2z^4)= | | 18=-9r | | 2t-0=15 | | 2(1x-3)=2x | | 6y+x=12 | | 36=-12b | | 4a-4=2a+34 | | 8n+(4n+5)=27 | | 0=11.0+-4.1(t) | | x+5-2=20 | | 3-4x=13-x+2x | | -47=a+34 | | 2=x-8/4 | | 15w^3+12w^2+35w+28= | | 3(2x-3)=4x(x+4) | | 3p+7p=-16+8p | | -10p+8=-9p | | -9x+10y=-9 | | X-85=-81 | | -10+7m=1-4m | | y=a^4+a^2-2 | | -8t=-9-9t | | -5g=-4g+-10 | | -96=-57+n | | 5x^2-40x-2=0 | | 5(d+2)=5d-1 | | 4u=u+6 | | -5=3+2x |